PENULISAN KONSONAN RANGKAP (SOKUON) PADA BAHASA PERCAKAPAN DALAM KOMIK BAHASA JEPANG - Masilva Raynox Mael (Universitas 17 Agustus 1945 Surabaya, 2021)
Double Consonant writing in Japanese marked by Hiragana or Katakana written (?/?). Sokuon has been used many in daily comic conversation to emphazise or strengthen the speech. As the consequence, the outcome of Japanese written becomes unstandard since there is morphologically change. That is why a research has been done using comic titled Crows volume 1 by Takahashi Hiroshi to represent Japanese Comic that generally has the same sokuon written structure in daily conversation. Analysis result shows there is 1 sokuon written in the beginning, 7 sokuons in the middle, and there area 17 sokuons in the end, also there area 16 sokuons in between 2 words. Those data has been analyzed using The Prominen Theory and The Shukuyaku-kei Formation Theory. Future expectation is to expand this research through other aspect of speech that use sokuon seen from the context and function aspect. Keywords: Double Consonant, Sokuon, Daily Language Communication, Comic.